Potential Mechanisms of Yanghe Decoction in the Treatment of Soft Tissue Sarcoma and Arteriosclerosis Obliterans Based on Network Pharmacology - Zhai, Yiran; Jiang, Shiqing; Li, Binyi; Miao, Lili; Wang, Jie; Li, Shanshan (Chinese medicine and natural products, 2022)
Objective The objective of this study was to investigate potential mechanisms of Yanghe Decoction (, YHD) in treating soft tissue sarcoma (STS) and arteriosclerosis obliterans (ASO) based on the use of network pharmacology.Methods Candidate compounds and potential targets were identified through the TCM Systems Pharmacology database and a comprehensive literature search. Related targets of STS and ASO were collected in the GeneCards database, DisGeNET database, and Drugbank database. Furthermore, The STRING 11.0 database was used to determine protein–protein interaction (PPI) networks; common targets were obtained and imported into Cytoscape 3.7.2. Then, a PPI network comprising common targets was drawn, and network topology analysis was performed to screen for key shared targets. Gene ontology functional enrichment analysis and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis of key shared targets were performed by using Metascape software. Subsequently, a compound–target–pathway network was constructed via Cytoscape 3.7.2.Results The following signaling pathways were found to be associated with the mechanisms of YHD in treating STS and ASO: AGE-RAGE signaling pathway, IL-17 signaling pathway; HIF-1 signaling pathway, TNF signaling pathway, interactions between cytokines and cytokine receptors, Th17 cell differentiation, and NOD-like receptor signaling pathway. Among the compounds and targets involved in these pathways, quercetin, luteolin, and kaempferol were found to be core compounds, and TNF, IL-6, and MAPK1 were found to be core targets.Conclusion Taken together, our findings elucidated that potential mechanisms of YHD in treating STS and ASO involved cellular proliferation/differentiation, angiogenesis, inflammation, immune responses, oxidative stress, and other related signaling pathways.
Keywords: soft tissue sarcoma; arteriosclerosis obliterans; network pharmacology; Traditional Chinese medicine; Yanghe Decoction